PACKAGING SOLUTIONS TO PROLONG SHELF LIFE OF GREEN PIGEON PEA KERNELS UNDER REFRIGERATED CONDITION - PRADIP A. BORKAR, AKSHAY R. MALI , AMIT R. DORKAR , ASHWINI M. CHARPE; RAJESH P. MURUMKAR (The Bioscan, 2018)
Green pigeon pea kernels (GPPK’s) are protein rich vegetable. GPPK of BDN-2001-2009 at 70 days of crop maturity was tested to improve shelf-life and reduced browning. 17 treatments of blanching temperature 75, 85, 95°C in combination with 1, 4, 7 min treatment duration and two packaging films polypropylene (PP) and low density polyethylene (LDPE) of 100, 200, 300 gauge were applied. Packets were stored at refrigerated condition (7-8°C; 80-85% RH). Observations were recorded at 10 days interval till 40th day for physiological loss of weight (PLW), firmness, color deviation, moisture content and sensory status. Experiment was conducted in BoxBehnken model and 17 treatments with 6 categoric factors giving 102 treatment combinations were studied. Optimized independent parameters for modified atmosphere packaging of GPPK by response surface methodology were 95°C blanching temperature, 6.70 min blanching time and 235 gauge packets. Predicted responses were 1.45% PLW, 4.41 N firmness, 55.69% color deviation, 58.67% moisture content and sensory status of 8.17. Blanching for 7 min at 95°C and packaging in 200 gauges PP, nearest to optimized treatment was found acceptable by HACCP standards at level-2 for microbial load with headspace composition of 12.6% O2 and 5.6% CO2 on 40th day under refrigerated storage.